Comparison of short-term results in THA patients with SuperPath® and the conventional approach for dysplastic OA of the hip - Hagio, Keisuke; Aikawa, Kazuhisa; Akiyama, Keisuke (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Although there have been many reports of comparative studies between SuperPath® and other approaches for THA with primary OA of the hip, there have been no reports of comparative studies of THA for secondary OA. The purpose of this study is to compare clinical outcomes and lower extremity recovery between THA of SuperPath® approach (Group S) and that of conventional posterior approach (Group C).Methods: Both 30 patients (Group S) and 36 patients (Group C) were investigated for clinical scores and recovery of lower limb function.Results: JOA scores showed no significant difference in preoperatively (group C: 46.5±9.2, Group S: 48.4±8.2, p=0.30), but at discharge (Group C: 76.8±4.3, Group S: 86.7±5.1, p